Asian monetary fund : getting nearer - Rana, Pradumna B. (2012)
The establishment of the ASEAN+3 Macroeconomic Research Office (AMRO) recently and the Chiang Mai Initiative Multilateralisation (CMIM) last year has shortened the road towards the Asian Monetary Fund (AMF). But still, don’t expect the AMF for at least another five years.